IMPACT OF DIGITAL MARKETING ON CONSUMER PURCHASING BEHAVIOR ON HERBAL COSMETIC PRODUCTS WITH REFERENCE TO PIMPRI CHINCHWAD CITY - Chaudhari, Madhuri; Jain, Apurva; Sanmath, Shivanand (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Companies spend a lot of money on digital relationships with potential customers. In the modern world, digital marketing has become an important part of companies’ marketing plans. It is an effective tool that enables companies to successfully convey their brand message to a large audience. Digital marketing has significantly changed consumer behavior. This study focus on digital marketing - changes in consumer behavior under the influence of digital technology. The aim of this study is to analyze the effects of digital marketing on consumer buying behavior and to determine whether consumers should be aware of digital marketing and how it affects their purchasing. According to the findings of the decision survey, the majority of people are familiar with digital marketing. They embrace digital marketing and that has influenced their decision to shop online. To increase the number of customers for online businesses and increase the volume of goods and services they sell and help them save time.